2021
DOI: 10.1007/s10518-021-01120-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the fragility curves for Italian residential masonry and RC buildings

Abstract: The Department of Civil Protection (DPC), in compliance with the EU decision 1313/2013 and at the request of the Sendai Framework for Disaster Risk Reduction 2015–2030 to update the disaster risk assessments by various countries, released the latest National Risk Assessment for Italy at the end of 2018. Specifically, as regards the seismic risk assessment, six research units belonging to two centres of competence of the DPC collaborated under its guidance to update the risk maps of the Italian residential heri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 43 publications
(143 reference statements)
0
18
0
Order By: Relevance
“…In the literature, there are many works related to risk analysis, either in a broad sense or to some specific factor. Some specific studies on the vulnerability can be found in [1][2][3][4][5][6][7][8][9][10] and on the exposure in [11,12] Regarding the costs analyses, some works are reported in [13,14] and on the multi-criteria, there are [15][16][17][18][19].…”
Section: Caesar II (Complementary Analyses For Emergency Planning Based On Seismicmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, there are many works related to risk analysis, either in a broad sense or to some specific factor. Some specific studies on the vulnerability can be found in [1][2][3][4][5][6][7][8][9][10] and on the exposure in [11,12] Regarding the costs analyses, some works are reported in [13,14] and on the multi-criteria, there are [15][16][17][18][19].…”
Section: Caesar II (Complementary Analyses For Emergency Planning Based On Seismicmentioning
confidence: 99%
“…In the CAESAR II tool, the hazard parameter used is the PGA (peak ground acceleration), because of the availability of PGA-Level Damage fragility curves developed by the authors, whose reliability has been tested in other applications. Although hazard may be defined by different parameters relevant to seismic motions, such as spectral shape, duration and energy content, PGA has been chosen since it represents the most consolidated quantity used by the Italian community [1][2][3]5]. In this sense, the available PGA data sufficiently characterize the entire national territory, while the use of different parameters can result in less reliable analyses.…”
Section: Hazardmentioning
confidence: 99%
See 1 more Smart Citation
“…Residential buildings account for 75% of the total stock in Europe, of which 64% consists of single-family houses, i.e., detached, semi-detached, or terraced houses (the rest being apartment blocks) [1,3]. In Italy, 87% of residential buildings correspond to masonry and reinforced concrete (r.c.)…”
Section: Introduction 1seismic Risk Of Residential Buildingsmentioning
confidence: 99%
“…The latest seismic events affecting Italian territory revealed that the poor seismic performance of masonry buildings resulted in high damage and losses (i.e., central Italy, 2016 [1,2], including also the positive effects of preventive actions [3], Emilia 2012 [4,5], L'Aquila 2009 [6,7], Molise 2002 [8][9][10], and Umbria and Marche 1997 [11,12]). The recent seismic risk assessment of residential buildings in Italy also demonstrated the significant economic loss and loss of human lives connected to the performance of existing, and particularly masonry, buildings [13,14].…”
Section: Introductionmentioning
confidence: 99%